EGFR inhibition in NSCLC: New findings…. and opened questions?. (April 2017) - Passiglia, Francesco; Listì, Angela; Castiglia, Marta; Perez, Alessandro; Rizzo, Sergio; Bazan, Viviana; Russo, Antonio
Abstract: The targeted inhibition of epidermal growth factor receptor (EGFR) has represented a milestone in the treatment of lung cancer. Several studies convincingly and consistently demonstrated a significant superiority of EGFR-TKIs over standard platinum-chemotherapy in EGFR-mutated NSCLC patients, leading to the sequential approval of gefitinib, erlotinib and afatinib as new standard first-line clinical treatment. To date we are witnessing a second revolution in the management of EGFR-positive NSCLC thanks to the development of new treatment strategies aiming to overcome acquired resistance to TKIs and ultimately improve patients' outcomes. In this review we summarize the most important recent findings regarding EGFR-inhibition in NSCLC, highlighting the current unsolved questions on the selection of the best TKI in first-line, which therapy can be combined with upfront EGFR-TKIs, how to overcome acquired resistance, and which are the clinical applications of liquid biopsy.